Household Service Quality: Insights from Quality Management Systems and Cluster Organization Models: Kualitas Layanan Rumah Tangga: Wawasan dari Sistem Manajemen Mutu dan Model Organisasi Klaster - Abibullaevna, Yerejepova Bibisara (Indonesian Journal of Law and Economics Review, 2024)
This study explores the dynamics of quality management systems and cluster organization models within the household service industry. Using keywords such as household service quality, assessment methods, factors, resources, clusters, and models, we investigate the efficacy of the five-star quality management model and algorithms for evaluating quality management processes. Our findings reveal crucial insights into meeting consumer expectations, understanding social factors, and optimizing resource utilization for improved service delivery. The implications suggest the potential for enhanced collaboration, innovation acceleration, and market responsiveness, highlighting avenues for future research and industry development. Highlights: Improved collaboration: Integrating quality systems and clusters boosts service quality and customer satisfaction. Faster innovation: Algorithms speed up quality assessment, fostering industry adaptation. Responsive markets: Understanding social factors enhances market competitiveness and sustainability. Keywords: Household Service Industry, Quality Management System, Household Service Quality, Model, Cluster.